Cosensitization of porphyrin dyes with new X type organic dyes for efficient dye-sensitized solar cells. (April 2019) - Jia, Hai-Lang; Chen, Yu-Chao; Ji, Liang; Lin, Li-Xia; Guan, Ming-Yun; Yang, Yi
Abstract: Herein, we developed two new X type D-(π-A)2 organic dyes JX1 and JX2, and cosensitized with porphyrin dyes JP1 and JP3 for DSSCs. For JX1 and JX2, the electron donors were modified with alkylbenzene containing long carbon chains, which can effectively inhibit dye aggregation and reduce charge recombination. Meanwhile, two benzoic acid groups were used as anchoring groups, we can see that the binding ways of JX1 and JX2 were both tetradentate mode from FT-IR analysis, this strategy helps to enhance the adsorption stability of dye molecules and increase the amount of dye adsorption. The DSSC based on JX1 showed a PCE of 3.67%, and the DSSC based on JX2 showed a higher PCE of 4.36%, the difference between them should be mainly attributed to the higher dye adsorption and better light-harvesting ability of JX2. In addition, developing new and efficient dyes is not the only way to improve performance of DSSCs, cosensitization is also one of the effective ways to achieve this goal. Although porphyrin has good optical absorption properties, there is a weak absorption in the range of about 500–600 nm, cosensitization can make up for the defect in this range well. After cosensitization, the effects on light-harvesting ability, photovoltaic performance and charge recombination were studied in detail. Obviously, the DSSC based on JP3+JX2 showed excellent light response and a high PCE of 8.08%, which exhibited remarkable PCE improvements of 26% compared with the DSSC based on JP3 (6.40%). The results show that method of filling up porphyrin dye with suitable organic dyes can effectively improve the performance of DSSCs. Graphical abstract: The strategy of filling up the voids between porphyrin dyes with suitable cosensitizer can effectively improve the performance of DSSCs. Highlights: The X type organic dyes can enhance binding strength and increase electron extraction channels. Suitable cosensitization can suppress electron recombination. An excellent light response and a high PCE of 8.08% have been achieved for the DSSC based on JP3+JX2.